PENGEMBANGAN INOVASI PRODUK YANG BERDAYA SAING CYPHO JELLY DRINK - Casnan Casnan; M. Syamsul Maarif; Yandra Arkeman (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2014)
Beverage industry is a segment of the food industry wich is quite the trend thesedays. The industry is rapidly innovate, make changes, and have more buzzing dynamics thanthe other segments. Beverage industry was seen easier to adopt scientific concepts regardingfood ingridien functionality when compared to other food industries. Beverage industry is nolonger producing beverages to satisfy thirst, but many offer the concepts and features diversefunctionality. Eggplant Netherlands (Cyphomandra betecea Sendt.) Rich in provitamin Agood for eye health and vitamin C to treat thrush and increase endurance. Essentialminerals, such as potassium, phosphorus and magnesium were able to keep and maintaingood health. High fiber of the dutch eggplant benefit prevent cancer and constipation. Andone of the advantages of other dutch eggplant is capable of lowering high blood pressure.Beverage industry needs to be developed as the Indonesian original product that utilizeslocal commodities dutch eggplant is Cypho Jelly Drink beverages functional raw materialsbased local eggplant netherlands (Cyphomandra betecea Sendt.) lowering high bloodpressure.